Skrining Sarkopenia dan Gangguan Metabolik: Investasi Kesehatan Lansia Denpasar - I Putu Arya Giri Prebawa; Ketut Wahyudiana Sudana; Ni Made Puspa Dewi Astawa (Warmadewa University Press, 2025)
The elderly population in Indonesia continues to increase significantly every year. Common health problems experienced by the elderly are decreased motor function, known as sarcopenia, and metabolic disorders. Sesetan Village in Denpasar is one of the areas with the highest elderly population. This high number of elderly poses special challenges in the areas of health and environment. As a solution, counseling and screening of metabolic disorders and sarcopenia were conducted for posyandu cadres and the elderly, along with socialization of household waste sorting. The targets of this activity were posyandu cadres and the elderly in the Banjar Dinas Taman Sari neighborhood. This activity includes coordination with the head of the neighborhood and coordinator of posyandu cadres, counseling, health screening, and socialization of household waste sorting. Partners in this program are posyandu cadres and the elderly in the Banjar Dinas Taman Sari Environment, Sesetan Village, South Denpasar District. The priority problems addressed were metabolic disorders and sarcopenia. The methods used include counseling, discussion, screening, and training. The program implementation began with a pretest to measure initial understanding, followed by counseling, training, discussion, and ended with a posttest. Health screening was carried out using blood sugar, cholesterol, and uric acid testing tools. The results of the activity showed an increase in knowledge of the elderly and family members about metabolic disorders and sarcopenia, obtained data related to the risk of metabolic disorders and sarcopenia in the elderly, and increased understanding and awareness of the importance of sorting household waste before disposal to landfills. Evaluation was carried out by asking posttest questions after the program implementation. This activity succeeded in motivating partners to take prevention and understand the importance of health in overcoming metabolic problems and sarcopenia in the elderly.